Bioethical aspects of informed consent for the use of vaccines in Pediatrics - Yenisey Triana Marrero; Vianed Marsán Suárez (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: Informed consent in Pediatrics is a progressive, consensual and dialogue-based decision-making process focused on a tripartite relationship (pediatrician-child-parents), under which the latter accept or do not accept the actions towards vaccination that have improved the prevention of different infectious diseases that affect the health of the child population and cause great morbidity, mortality and sequelae. Objective: To state the main bioethical aspects related to informed consent for the use of vaccines in Pediatrics. Material and Methods: A review of literature on the topic in Spanish and English was carried out using search engines such as Google Scholar. Also, 42 open access articles were consulted in the SciELO and Pubmed databases. The bibliography of the last 20 years was analyzed.  It mainly included articles published during the last 5 years (from 2000 to 2020). Development: Vaccines are preventive interventions that have a centuries-old history that demonstrates their goodness and effectiveness, but have posed ethical problems since the very beginning. Informed consent for their administration is not implemented with the same rigor in all regions of the world. Conclusions: Vaccination in Pediatrics is a frequent practice, so a duly drafted informed consent authorized by the legal guardians or the patient is necessary. It should include the explanation of the aims, the procedures to which the patient will be submitted, the possible damages and benefits, and the possible results.